Food and nutrition surveillance: Exploring facilitators and barriers to electronic registration in Brazil - Ricci, Joanna Manzano Strabeli; Sato, Priscila de Morais; Lourenço, Bárbara Hatzlhoffer (Informatics and Health, 2025)
Malnutrition is a leading global health challenge, worsened by dietary shifts toward the consumption of ultra-processed food. In Brazil, food and nutrition surveillance is integrated into the Primary Health Care (PHC) services of the Unified Health System (SUS) via the Food and Nutrition Surveillance System (Sisvan). Despite its potential for assessing population dietary trends and supporting public health policies, population coverage and use by health professionals and managers remain limited. This study aimed to identify facilitators and barriers to the use of Sisvan food intake markers in PHC, especially regarding data handling in collection, registration and analysis. A cross-sectional study was conducted in 2021, involving PHC managers and health professionals from all five Brazilian macro-regions. A questionnaire with closed- and open-ended questions was distributed electronically to assess the use of food intake markers, data entry routines, and practices for data analysis. Sociodemographic characteristics of participants were described. Thematic analysis was used to open-ended responses to identify barriers and facilitators. Among 301 participants, 78.1 % worked in municipalities that collected food intake markers, primarily using Sisvan forms (88.9 %). However, only 42.1 % reported routine data analysis at both individual and collective levels. The brevity and simplicity of the Sisvan forms and their integration with electronic systems were among the facilitators. Barriers were related to work overload, insufficient infrastructure, system slowness, and lack of professional training. Recommendations included enhancing system usability, expanding professional qualification programs, and fostering interprofessional collaboration. The findings highlight the underutilization of data on food intake markers for planning and decision making in PHC in Brazil, despite a significant proportion of participants acknowledging data collection. Addressing identified barriers could enhance Sisvan's potential to monitor dietary trends and guide public health interventions. This study underscores the need for targeted strategies, such as continuing education, better integration with electronic health records, and infrastructure improvements, to strengthen food and nutrition surveillance in Brazil. •Monitoring of dietary trends is feasible, but lacks routine data analysis in PHC.•Barriers include workload, system instability, and infrastructure gaps.•Professional training and electronic integration are key to improving the system.